Absenteeism and Indirect Economic Burden Associated With Primary and Secondary Hypogonadism: A Retrospective Matched Cohort Analysis of Employed, Commercially Insured Patients in the U.S. Issue 8 (August 2018) - Hepp, Zsolt; Kim, Gilwan; Lenhart, Gregory; Johnson, Barbara H.
Abstract : Objective: The aim of this study was to evaluate the indirect economic burden incurred by patients with primary and secondary hypogonadism (HG) compared with non-HG controls using real-world data. Methods: In this retrospective cohort study using a large US administrative claims database, adult males with primary or secondary HG were selected from 2010 to 2014. Non-HG controls had no evidence of HG from 2009 to 2014 and were matched on age, insurance type, and geographic region to HG patients. Outcomes included absenteeism and associated costs. Results: HG (vs non-HG) patients had a significant 15% increase in nonrecreational absenteeism hours (adjusted odds ratio 1.15, P = 0.002) and associated costs (2152 vs 1172, P < 0.001) post-index after adjusting for pre-period differences. Conclusion: The indirect economic burden of HG is significant. Further research is needed to test whether treatment with testosterone can help alleviate the indirect burden associated with HG.